Fitness and Aesthetics Hostel Gym Management - Sanjiban Bandyopadhay; Vivek Kumar; Satendra Singh (International Journal of Computer Science Languages, 2023)
Fitness & Aesthetics’ mission is to help people achieve their fitness objectives by offering training regimens and healthy living plans, as well as assistance with managing a club. By automating the current manual method with the use of digitized equipment and comprehensive computer software, it will provide the information of the Trainer, Gym, Facility, Workout Routines, and Time Slot and proceed into the administrative position, satisfying their requirements, in order to retain their vital data for a longer amount of time with easy access and modification. The required hardware and software are easily accessible and understandable. As previously said, a fitness and aesthetics website may raise awareness of a healthy lifestyle and its advantages and motivate users to achieve their fitness objectives in a safe, error-free manner. It can allow the user to concentrate on their exercise and healthy living habits rather than keeping record. Therefore, it will help businesses use their resources more effectively. The business may update its computerized records without entering the identical information twice. To learn the material, one need not get sidetracked by little details. The initiative essentially lays out how to do business for greater performance and customer service.
Keywords: Workout routines; attendance; gym facility; member administration; time slots; trainer; user membership